Information and communication technology integration and teaching mathematics in higher education - Tokanov, Mansur; Damekova, Saule; Kuttykozhayeva, Shakharzat; Abdoldinova, Gulsim; Smagulov, Yessengali (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
The purpose of the study is to develop a model for the application of information and communication technology in the teaching of higher mathematics at the level of school education. The leading method for studying this issue is testing developed by V.E. Milman